Perception of health, quality of life and functional capacity in adults and elderly after hospitalization due to complications of COVID-19 - a longitudinal study with 6-month follow-up - Débora Vieira de Araújo; Ana Laura Rodrigues de Lima; Erika de Cassia Santos Costa; José Maria Montiel; Angélica Castilho Alonso; Guilherme Carlos Brech (Universidade de São Paulo, 2023)
ABSTRACT The study aims to evaluate the perception of health, quality of life and functional capacity during six months after COVID-19-related hospitalization. This is a prospective longitudinal study carried out at Universidade São Judas Tadeu (USJT) in partnership with the Instituto Ânima Brasil. Thirteen adult participants, including young and older adults, were evaluated, had a confirmed diagnosis of COVID-19 and were hospitalized. A characterization and interdisciplinary questionnaire built by the researchers was used to assess health perception, quality of life, and functional capacity of participants. In this study, participants were followed for a 6-month period and the main results obtained were: the identification of a significant increase in walking time after three months (p=0.002) as well as an improvement in the perception of quality of life (p=0.002). In addition, the levels of tiredness and physical activity were evaluated; the mean responses were "little tired" and "irregularly active," respectively, and remained unchanged over six months. Considering that patients who were hospitalized due to COVID-19 showed a reduction in the perception of quality of life and walking time soon after the hospital period, it was identified that over time they tend to improve these perceptions.